Circ-Sirt1 inhibits proliferation, induces apoptosis, and ameliorates inflammation in human rheumatoid arthritis fibroblast-like synoviocytes - Suhua Zhang; Jun Zhao; WuQiang Ma (Taylor & Francis Group, 2021)
Rheumatoid arthritis (RA) is a chronic inflammatory disease related to abnormal activation of fibroblast-like synovium cells (FLS) with apoptosis, inflammation, and oxidative damage. Circular RNA Sirt1 (circ-Sirt1) is an abundant circRNA, exerts the function in inhibiting inflammation. However, little is known about the roles of circ-Sirt1, if any, in RA. The present study aimed to investigate the biological roles and mechanism of circ-Sirt1 on cell inflammation in RA-FLS MH7A cell line. This study showed circ-Sirt1 inhibited the proliferation and induced apoptosis of MH7A cells. Overexpression of circ-Sirt1 decreased of the levels of interleukin (IL)-1β and IL-6, tumour necrosis factor (TNF)-α, and matrix matalloproteinases (MMP)-1 and MMP-3 in MH7A cells. In addition, overexpression of circ-Sirt1 increased the expression of Sirt1, Nrf2, HO-1, IκBα, GCLC and GCLM, and decreased the ratio of acetylated NF-κB to normal NF-κB, and the expression of AP-1, COX-2 and HMGB1. Moreover, the expression of Keap1 and the ratio of acetylated NF-κB to normal NF-κB were partially increased and the Nrf2 and Sirt1 were partially reduced by siSirt1. Additionally, circ-Sirt1 overexpression promoted the activation of Sirt1 signal pathways by upregulating miR-132. In conclusion, the protective effect of Circ-Sirt1 on MH7A depends on inhibiting cell proliferation, promoting apoptosis and miR-132-mediated Sirt1 pathway to reduce inflammation.